Global symmetries and [Formula: see text] SUSY - McOrist, Jock (Lett Math Phys, 2017)
We prove that [Formula: see text] theories that arise by taking n free hypermultiplets and gauging a subgroup of [Formula: see text] , the non-R global symmetry of the free theory, have a remaining global symmetry, which is a direct sum of unitary, symplectic, and special orthogonal factors. This implies that theories that have [Formula: see text] but not [Formula: see text] global symmetries, such as Gaiotto’s [Formula: see text] theories, are not likely to arise as IR fixed points of RG flows from weakly coupled [Formula: see text] gauge theories.